2009
DOI: 10.1055/s-0029-1210546
|View full text |Cite
|
Sign up to set email alerts
|

Androgens, Bone Mineral Content and Hyperostosis Frontalis Interna in Pre-Menopausal Women

Abstract: Greater than normal bone mineral content, bone width of the radius measured by photon absorptiometry and bone mineral content to bone width ratio found in women with hyperostosis frontalis interna pointed on a generalized alteration of the skeletal system. An increase in serum dehydroepiandosterone, its sulphate and testosterone levels and a significant correlation between serum free dehydroepiandosterone and bone mineral content in subjects without any sign of hirsutism or obesity suggested an involvement of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 6 publications
0
5
0
1
Order By: Relevance
“…Deranged bone mineral metabolism in premenopausal women with an increase in dehydroepiandrosterone and testosterone levels showed the potential role of androgens in metabolic bone disorders [24]. Skeletal muscle tissue is in a relatively hypoxic environment which can induce subtle metabolic derangements that can manifest as tumours.…”
Section: Discussionmentioning
confidence: 99%
“…Deranged bone mineral metabolism in premenopausal women with an increase in dehydroepiandrosterone and testosterone levels showed the potential role of androgens in metabolic bone disorders [24]. Skeletal muscle tissue is in a relatively hypoxic environment which can induce subtle metabolic derangements that can manifest as tumours.…”
Section: Discussionmentioning
confidence: 99%
“…Males with hormonal irregularities, such as atrophic testis and/or feminism were found to have HFI of variable severity [9,12]. On the other hand, it has been shown that HFI is related to elevated androgen levels in pre-menopausal women [26]. At present, the most acceptable hypothesis regarding HFI pathogenesis is hormonal imbalance of the gonads.…”
Section: Discussionmentioning
confidence: 99%
“…Increases of 72% free testosterone, 17% testosterone 16% androstenedione were all reported in obese females as well as increases of 47% estradiol, 89% free estradiol and 47% estrone (Key et al, ). HFI has also been associated with significant increases of androgen levels, including free testosterone (Fulton et al, ) as well as serum DHEA, DHEA‐S and total testosterone in past studies of pre‐menopausal females without signs of virilism (Kollin & Fehér, ). Androgenicity is highly dependent on FT and the associated lower levels of SHGB (Abdel‐Rahman & Hurd, ).…”
Section: Discussionmentioning
confidence: 99%